Strategic Development of Commercial Real Estate Company KCRE CEE Expansion in internationalization framework - Pavlas, Michal; Jaklová, Martina L.; Tomas, Kubiny; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
Primary aim of this master thesis is to depict an emergence of a professional service firm performing its' activities on the commercial real estate market in the Czech republic and to project future development in CEE region confirming existence of factors leading to fast internationalization of a professional service firm concept with specific attention to a born global concept. The work aims to identify factors of a PSF growth in various dimensions and in various specific markets as well as best practices of other globally operating structures. While the theoretical part of the thesis presents principles of a professional service firm's (PSF) function, commercial real estate market and internationalization, the practical part assumes application and implications for the company Kenoby Group ltd. (KCRE). The academic enrichment of research is derived from the three-dimensional interconnection of the concepts of Professional Service Firm, Commercial Real Estate and Internationalization, Born Global respectively.
Vedoucí práce: Martina L. Jaklová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Rok obhajoby 2011
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses